THE ANTI-TB DRUG SENSITIVITY OF Mycobacterium tuberculosis FROM CEREBROSPINAL FLUID AND BONE TISSUE BIOPSY SPECIMENS OF PATIENTS SUSPECTED TUBERCULOUS MENINGITIS AND SPINAL TB IN Dr SOETOMO HOSPITAL INDONESIA - Mertaniasih, Ni Made; Kusumaningrum, Deby; Koendhori, Eko Budi; Harijono, Sugeng; Arky, Catur Endra; Putri, Jayanti; Urifah, Hanik (Indonesian Journal of Tropical and Infectious Disease, 2014)
Tuberculous meningitis (TBM) is an infection of meningens which potentially life threatening with significant morbidity andÂ mortality. Spinal TB has the same problem with TBM, infection in bone and joint, the delayed diagnosis worsens the prognosis. TheÂ rapid and accurate diagnosis plus promt adequate treatment is essential for the good outcome. The aim of this research is to study thefirst line drug sensitivity of Mycobacterium tuberculosis isolated from specimens of cerebrospinal fluid from suspected tuberculousÂ meningitis patients and bone tissue biopsy from suspected spinal TB patients. The method of this research is TB Laboratory examinationÂ in Department of Clinical Microbiology â Dr. Soetomo General Hospital, Indonesia, using the gold standard liquid culture methodÂ MGIT 960 System (Becton Dickinson) and solid culture method with Lowenstein-Jensen medium. The specimens CSF from 50Â TBM patients at January 2013 until May 2014. Positive isolate detection of Mycobacterium tuberculosis complex were 11 isolatesÂ (22%), which sensitivity 100% (11/11 isolates) to Rifampin (R), Pyrazinamide (Z), Ethambutol (E), and Streptomycin (S); one isolateÂ resistant to Isoniazid, sensitivity to Isoniazid 90,90% (10/11); and received 21 specimens of bone tissue biopsy which positive 5 isolates(23%), all isolates sensitive 100% (5/5 isolates) to Rifampin and Pyrazinamide, and 1 isolates resistant to Isoniazid, Ethambutol, andÂ Streptomycin, in which sensitivity 80% (4/5 isolates) to Isoniazid, Ethambutol, and Streptomycin. The conclusion of this research isÂ positivity detection 22% of CSF specimens, and 23% of bone tissue biopsy were low. All isolates sensitive 100% to Rifampin andÂ Pyrazinamide, and 80-90% sensitive to Isoniazid.